La revue : un lieu de contestation ? - Wolf Feuerhahn; Olivier Orain (Tracés, 2018)
It can be tricky to view human and social science journals (SHS in French) as a homogeneous whole. Through the case of the Revue d’histoire des sciences humaines (RHSH), founded in 1999, we would like to shed some light on the macroscopic characteristics of the SHS publishing community. Indeed, the history of human and social sciences is a very small field of study, but its objects partake to much broader issues. Journals focusing on mainstream disciplines with many members (such as sociology, psychology, economics, geography, etc.) regularly publish historical or retrospective dossiers. The consequence of this is that their approach of their objects is clearly disciplinary and often instrumental, which is expressed through a vast array of – often genealogical – tools, from hagiography to the symbolic annihilation of an author or a concept. The RHSH advocates for a transversal approach to the history of human sciences, without neglecting the disciplinary evolutions that have marked their development. Refusing to endorse canons and traditions, it seeks to put them back in their historical frame by varying the analytical scales and focal points (history of publishing, places of knowledge, institutions, transnational exchanges, etc.). Its history highlights both the difficulty and the need to challenge the hierarchy between disciplines.